Hubungan kemampuan visuospasial dengan kemampuan anatomi - M. Ghilman Nurizzan (Universitas Syiah Kuala, 2021)
Along with the development of medical learning methods, anatomy remains one of the most difficult subjects to understand among other basic medical education sciences. The study of the structure of the human body, its parts and the relationships between these parts involves the processing of visuospatial information, namely the understanding of the form, location, and position of an object against other objects in 3-dimensional space. The purpose of this research is to find out how the relationship between visuospatial abilities and anatomical abilities of the students of the Faculty of Medicine, Sebelas Maret University